Essential DNA sequence for the replication of Rts1. - Itoh, Y (1987)
The promoter sequence of the mini-Rts1 repA gene encoding the 33,000-dalton RepA protein that is essential for replication was defined by RNA polymerase protection experiments and by analyzing RepA protein synthesized in maxicells harboring mini-Rts1 derivatives deleted upstream of or within the presumptive promoter region. The -10 region of the promoter which shows homology to the incII repeat sequences overlaps two inverted repeats. One of the repeats forms a pair with a sequence in the -35 region, and the other forms a pair with the translation initiation region. The replication origin region, ori(Rts1), which was determined by supplying RepA protein in trans, was localized within 188 base pairs in a region containing three incII repeats and four GATC sequences. Dyad dnaA boxes that exist upstream from the GATC sequences appeared to be dispensable for the origin function, but deletion of both dnaA boxes from ori(Rts1) resulted in reduced replication frequency, suggesting that host-encoded DnaA protein is involved in the replication of Rts1 as a stimulatory element. Combination of the minimal repA and ori(Rts1) segments, even in the reverse orientation compared with the natural sequence, resulted in reconstitution of an autonomously replicating molecule.